New perspectives in patient education for cardiac surgery using 3D-printing and virtual reality - Grab, Maximilian; Hundertmark, Fabian; Thierfelder, Nikolaus; Fairchild, Matthew; Mela, Petra; Hagl, Christian; Grefen, Linda (Frontiers in Cardiovascular Medicine, 2023)
Background Preoperative anxiety in cardiac surgery can lead to prolonged hospital stays and negative postoperative outcomes. An improved patient education using 3D models may reduce preoperative anxiety and risks associated with it. Methods Patient education was performed with standardized paper-based methods (n = 34), 3D-printed models (n = 34) or virtual reality models (n = 31). Anxiety and procedural understanding were evaluated using questionnaires prior to and after the patient education. Additionally, time spent for the education and overall quality were evaluated among further basic characteristics (age, gender, medical expertise, previous non-cardiac surgery and previously informed patients). Included surgeries were coronary artery bypass graft, surgical aortic valve replacement and thoracic aortic aneurysm surgery. Results A significant reduction in anxiety measured by Visual Analog Scale was achieved after patient education with virtual reality models (5.00 to 4.32, Δ-0.68, p < 0.001). Procedural knowledge significantly increased for every group after the patient education while the visualization and satisfaction were best rated for patient education with virtual reality. Patients rated the quality of the patient education using both visualization methods individually [3D and virtual reality (VR) models] higher compared to the control group of conventional paper-sheets (control paper-sheets: 86.32 ± 11.89%, 3D: 94.12 ± 9.25%, p < 0.0095, VR: 92.90 ± 11.01%, p < 0.0412). Conclusion Routine patient education with additional 3D models can significantly improve the patients' satisfaction and reduce subjective preoperative anxiety effectively.